Sharia-Based Zakat Fitrah Management to Support the Mustahiq Economy During Eid al-Fitr - Hasby, Muhammad; Siregar, Saparuddin; Arsyadona, Arsyadona (Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this article is to provide an explanation of the management of zakat fitrah, that zakat fitrah is very important to be paid and implemented. A strong understanding of zakat fitrah, an understanding from a religious perspective about zakat fitrah and the obligation to carry it out. This article is also done to find out the values of zakat fitrah and its relation to the socio-economy, so here we will prove its suitability. This article is also theoretical and conceptual in nature where we will present theories about zakat from various sources and look deeper to get appropriate results. Whatever the form, the most important thing is the awareness of the obligation of zakat (muzakki). And know how zakat fitrah affects during Eid al-Fitr.